Binge-eating disorder: emerging treatments for a new diagnosis. Issue 4 (August 2016) - Tsappis, Michael; Freizinger, Melissa; Forman, Sara F.
Abstract : Purpose of review: This review provides an update on the new Diagnostic and Statistical Manual (DSM) diagnosis of binge-eating disorder (BED) by presenting diagnostic criteria, associated risk factors and co-morbidities, and tools for assessment. An update on the currently available evidence-based treatments for adolescent BED is provided to help with the coordination of treatment planning for identified patients with this condition. Recent findings: BED is now officially included in the DSM. Research with youth has begun to show improvement from treatments such as cognitive behavioral therapy, previously shown to be useful in adults. Summary: BED is common and often begins during youth. The availability of diagnostic criteria, along with increasing knowledge about the condition and available treatments, is expected to result in improved identification and management in younger patients.